Biodiversity and Education for Sustainable Development - Castro, Paula; Azeiteiro, Ulisses Miranda; Bacelar-Nicolau, Paula; Leal Filho, Walter; Azul, Anabela Marisa (Springer International Publishing Imprint: Springer, 2016)
Biodiversity and Education for Sustainable Development (ESD): Tendencies and Perspectives -- Conservation of Biological Resources: Why it Matters -- Urban Biodiversity and Cities’ Sustainable Development -- Education on Biodiversity in the Polar Regions -- Teaching Mycology Worldwide -- Bugs and Society -- Science and Education at the Centre for Invasion Biology -- Engaging Society to Fight Invasive Alien Plants in Portugal - One of the Main Threats to Biodiversity -- Engaging ODL Students with Biodiversity Issues: A South African Case Study on the Role of ESD -- Education for Sustainability in the Context of Community Forestry.
Description based upon print version of record